Multiscale Thermo-Hydro-Mechanics of Frozen Soil: Numerical Frameworks and Constitutive Models - Malekzade Kebria, Mahyar (My University, 2024)
This study introduces numerical frameworks for simulating the interactions within soil systems subjected to freezing and thawing processes, crucial for addressing geotechnical challenges in cold regions. By integrating robust thermo-hydro-mechanical (THM), this research offers a general understanding and specific insights into the deformation, thermal, and moisture transport behaviors of freezing-thawing soils. The first part of this study presents a soil freezing characteristic curve (SFCC) adaptable to various computational frameworks, including THM models. The SFCC, enhanced by an automatic regression scheme and a smoothing algorithm, accommodates the dynamic changes in soil properties due to phase transitions. This model effectively captures the unique behaviors of different soil types under freezing conditions, addressing key factors such as freezing temperature, compaction, and mechanical loading. Building on this foundation, the second framework employs the phase-field method (PFM) coupled with THM to model the behavior of ice-rich saturated porous media. This approach advances the field by enabling distinct representations of the mechanical behaviors of ice and soil through a diffused interface, introducing anisotropic responses as the soil undergoes freezing. By integrating a transversely isotropic plastic constitutive model for ice, this method provides a tool for capturing the phase transition processes and the resulting mechanical responses of frozen soil. The third part extends these methodologies to model thaw consolidation in permafrost regions using a THM framework combined with phase field methods. This model incorporates internal energy functions and a multiscale modified Cam-Clay model within a damage phase field framework, adept at capturing the simultaneous effects of phase change and particle rearrangement. Through validation against experimental scenarios, this model demonstrates its effectiveness in understanding the microstructural evolution and plastic softening in thaw-sensitive soils, which is vital for enhancing infrastructure resilience under thaw conditions. Together, these integrated approaches represent a leap in the modeling and simulation of geotechnical behaviors in cold regions, offering potential applications in predicting and mitigating the impacts of climate change on permafrost and other freeze-thaw affected terrains.
Keywords: Frozen soil; THM; Phase-field; Thermo-Hydro-Mechanics; Thawing consolidation; Soil freezing characteristic curve; Multiscale; Freezing induced anisotropy; Computational; Porous media; Finite element; Cryo-Suction